2014
DOI: 10.1007/s10508-013-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Casual Sex Harm College Students’ Well-Being? A Longitudinal Investigation of the Role of Motivation

Abstract: Engagement in casual sex (or hooking up) is generally feared to have negative well-being consequences; however, empirical evidence is inconclusive, pointing toward potential moderators. Using self-determination theory (SDT), we hypothesized that well-being following hookups would depend on the type and level of motivation for hooking up. A university-wide sample of 528 undergraduates completed online surveys at the beginning (T1) and end (T3) of one academic year. After controlling for demographics, personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 87 publications
4
74
1
2
Order By: Relevance
“…To this end, some researchers have begun employing longitudinal methods to better understand changes over time. However, these studies primarily follow college students across a semester or an academic year (e.g., Fielder and Carey 2010;Vrangalova 2015), with some recent studies following individuals through developmental trajectories (e.g., Lyons et al 2015). Uncommitted sexual encounters have become somewhat of a hallmark of early or emerging adulthood Stinson 2010), and can begin in adolescence.…”
Section: Methodsological Approaches To Casual Sexmentioning
confidence: 99%
“…To this end, some researchers have begun employing longitudinal methods to better understand changes over time. However, these studies primarily follow college students across a semester or an academic year (e.g., Fielder and Carey 2010;Vrangalova 2015), with some recent studies following individuals through developmental trajectories (e.g., Lyons et al 2015). Uncommitted sexual encounters have become somewhat of a hallmark of early or emerging adulthood Stinson 2010), and can begin in adolescence.…”
Section: Methodsological Approaches To Casual Sexmentioning
confidence: 99%
“…They should also encourage adolescents to clarify their expectations about CSREs and under what conditions they could become a positive experience. Vrangalova (2015b) showed that having motivations that are not considered to be egosyntonic, such as social or internalized social pressure, was linked to worse psychological outcomes of genital CSREs. Some gender issues should be considered.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For example, in shortterm mating, the following female goals can be associated with positive outcomes and reactions: Assess partners' investment potential; test own attractiveness (mate value); gain opportunity to acquire higher investment; and acquire superior genes (Buss 1994;Buss and Schmitt 1993). In contrast, women who use short-term mating to establish relationships are often disappointed (Paul and Hayes 2002;Townsend 1995;Vrangalova 2015). In comparison, men's emotions motivate them to engage in low-cost sex with a variety of women when the opportunities present themselves and to be less concerned about long-term intentions (Salmon and Symons 2001).…”
Section: Sexual Strategies and Emotionsmentioning
confidence: 99%
“…In contrast, some studies report positive associations for both sexes between casual sexual relations and confidence, self-esteem, and sexual satisfaction (Campbell 2008;Owen and Fincham 2011). Vrangalova (2015) proposed that these mixed results suggest that there may be moderators that influence these dynamics, such as the different motivations that could lead to hooking-up.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation